Low amniotic uid index and the materno-fetal out come in 3rd trimester of pregnancy - Monir, Fahmida; Nazneen, Rumana; Akhter, Rumana; Begum, Tahmina; Kayum, AKM Abdul; Abedin, Mohshina; Zabin, Fahmida (Bangladesh Medical Journal, 2016)
Amniotic fluid volume is an indirect indicator of fetal well being. About 8% of pregnant women can have low amniotic fluid, with about 4% being diagnosed with oligohydramnios. Oligohydramnios can cause complications in about 12% of pregnancies that go past 41 wks of gestation. This cross-sectional observational study was carried out in the Department of Obstetrics and Gynaecology, BSMMU, Dhaka from July 2010 to December 2010 on 55 admitted pregnant mother of 28-40 weeks gestational age with low amniotic fluid index (<8cm) with or without medical disorders specially during and after delivery along with its impact on mode of termination of pregnancy & complications of the fetus. Most of the mother (64%) had mild oligohydramnios. Most of them were < 37weeks of gestation and 69.1% of them had to undergo caesarean section as there mode of delivery. The indications were mostly (66%) due to less fetal movement, IUGR, previous C/S, malpresentation etc. The current study showed significantly higher rate (65.5%) of low birth weight resulting from the low AFI. The APGAR score less than 7 in 5 minute was significantly higher in severe oligohydramnios group and majority of the neonate experienced complications like RDS (13%), meconeum aspiration (21%) with admission in neonatal ward (54%). Low AFI has poorer prognosis to some extent with maternal as well as fetal outcome. It is responsible for a significantly higher rate of caesarean section & also associated with low birth rate along with low APGAR score and increase in neonatal complications. Bangladesh Med J. 2015 Jan; 44 (1): 16-20